Spatiotemporal dynamics of crop water use and groundwater depletion under the winter wheat–summer maize rotation system in Henan Province, China - Zhang, Zhao; Wang, Jing; Ning, Jing; Ti, Jinsong (Frontiers in Plant Science, 2025)
IntroductionHenan Province plays a pivotal role in ensuring China’s food security through its extensive winter wheat–summer maize rotation system. However, excessive groundwater extraction has become a critical constraint on sustainable agricultural development.MethodsThis study quantitatively analyzed the spatiotemporal dynamics of crop water use and groundwater depletion across Henan from 1961 to 2020 using a water balance framework that integrates crop evapotranspiration (ETc), effective precipitation (Re), irrigation water requirement (Iwr), and net groundwater consumption (NGWC).Results and DiscussionResults showed distinct and opposite trends in ETc between the two crops: winter wheat exhibited increasing ETc under climate warming, while summer maize experienced a decline driven by improved water-use efficiency. Effective precipitation decreased during key growth stages, leading to increased irrigation demand for winter wheat but a reduction for summer maize. Winter wheat remained the dominant driver of groundwater depletion, consuming three to four times more groundwater annually than maize. However, since 2010, maize groundwater use has risen sharply, intensifying water stress in the central–northern plains. To alleviate overexploitation, a dual strategy combining winter wheat fallowing and summer maize water conservation is proposed. These findings provide a scientific foundation for optimizing cropping patterns and improving water resource sustainability in major grain-producing regions of North China.